1* and 2nd step characteristics proceeding the sprint start in amputee sprinting - Strutzenberger, G.; Brazil, A.; von Lieres und Wilkau, H.; Davies, J. D.; Funken, J.; Müller, R.; Exell, T.; Willson, C.; Willwacher, S.; Potthast, W.; Schwameder, H.; lwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate I* and 2"d stance phase spatio-temporal and ground reaction force (GRF) parameters of four unilateral transtibial amputee (AMP) and nine able-bodied (AB) sprinters. Data were collected using a 3D motion capture system (Vicon, 250 Hz) and two force plates (Kistler 1000 Hz). Aside from flight time (d=0.32) and step width (d=0.60), all spatio-temporal parameters were significantly lower for the AMP compared to the AB athletes for both limbs. Peak horizontal GRF and relative impulse were significantly decreased for the AMP group, while the peak vertical GRFs were significantly decreased for the 1' (affected limb) but increased for the 2"6 step (intact limb), with the relative vertical impulse data being similar. Therefore running prostheses appear to limit the performance of AMP compared with AB sprinters.